Determination of torasemide in human plasma and its bioequivalence study by high-performance liquid chromatography with electrospray ionization tandem mass spectrometry - Lin Zhang; Rulin Wang; Yuan Tian; Zunjian Zhang (Journal of Pharmaceutical Analysis, 2016)
A sensitive and selective method using high-performance liquid chromatography coupled with electrospray ionization tandem mass spectrometry (HPLC–ESI–MS) to determine the concentration of torasemide in human plasma samples was developed and validated. Tolbutamide was chosen as the internal standard (IS). The chromatography was performed on a Gl Sciences Inertsil ODS-3 column (100 mm×2.1 mm i.d., 5.0 µm) within 5 min, using methanol with 10 mM ammonium formate (60:40, v/v) as mobile phase at a flow rate of 0.2 mL/min. The targeted compound was detected in negative ionization at m/z 347.00 for torasemide and 269.00 for IS. The linearity range of this method was found to be within the concentration range of 1–2500 ng/mL (r=0.9984) for torasemide in human plasma. The accuracy of this measurement was between 94.05% and 103.86%. The extracted recovery efficiency was from 84.20% to 86.47% at three concentration levels. This method was also successfully applied in pharmacokinetics and bioequivalence studies in Chinese volunteers.